Analysis of the financial risks of the Ukrainian railway transport - Kravchenko, O.O. (Економіка промисловості, 2017)
The object of the paper is the financial risks of the railway transport. Today the financial situation of Ukraine's railway transport tends to deteriorate due to the systemic crisis of the national economy, the severance of existing economic ties, the critical wear and tear on non-negotiable assets, as well as an ineffective financial management. This led to the complexities of the formation of sufficient financial resources, the growth of financial risks and, as a result, the reduction of the international ratings. It is shown that little attention is paid to the risks, arising in the course of operating activities in the JSC ‘Ukrzaliznytsia’.The paper analyzes financial risks of Ukrainian railway transport (financing of operating activities, liquidity, interest, credit and currency). The analysis showed that the industry is facing problems related to the financing of operating activities, providing the necessary level of liquidity and, consequently, the cost of the resources involved. This leads to a decrease in the ability of Ukrzaliznytsia to carry out the operational activities, reduce its effectiveness and, as a result, further deterioration of the financial condition.In order to improve the financial situation and reduce the financial risks of railway enterprises, the directions of their reduction are offered: optimization of the structure of financial resources by reducing the share of borrowed funds, limiting the amount of high-risk financial transactions, limiting the volume of current assets in the form of low liquid and illiquid assets, rationalizing the policy of managing financial instruments, implementation of scientifically sound financial management system. The strategy and tactics for managing financial risks of the railway enterprises should be based on the balance between expected benefits and possible risks. Доведено, що погіршення фінансового стану підприємств залізничного транспорту призвело до дефіциту фінансових ресурсів. Визначено, що наслідком неефективного управління фінансами стало збільшення ризиків «Укрзалізниці». Проведено аналіз динаміки основних фінансових ризиків залізничного транспорту та їх впливу на формування фінансових ресурсів галузевих підприємств. Показано, что ухудшение финансового состояния предприятий железнодорожного транспорта привело к дефициту финансовых ресурсов. Определено, что следствием неэффективного управления финансами стало увеличение рисков «Укрзализныци». Проведен анализ динамики основных финансовых рисков железнодорожного транспорта и их влияния на формирование финансовых ресурсов отраслевых предприятий.